Analysis of Strategic Partnership Strategy to Accelerate the Business Growth of Pertamina - Diandra, Didip; Putra, Ebit (JOURNAL OF BUSINESS STUDIES, 2019)
This reseach analyze the strategic partnership strategy to accelerate the business growth of Pertamina, in another word to explain an effect of non-financial performance of Pertamina. The objectives of study is to reveal the current strategic partnership strategy that implemented by Pertamina and to recommend the advance strategic partnership to accelerate their business growth. This research used qualitative research approach and explanatory method which employs both primary data and secondary data to gauge the impacts of strategic partnership onto Pertamina. The result of analysis shows that strategic partnership contributes moderately towards acceleration of the business growth of Pertamina.